(untitled) (Web of Teachers: Inderscience Research, 2023)
This article discusses the integrative approach to mother tongue education at school. The article gives ideas on how to teach students to sort information from a young age by connecting the science of the mother tongue with the science of informatics, how to create self-awareness in the digital world, and how to use digital tools. It is written about the importance of assignments in school textbooks.